Ibrutinib for therapy of steroid-refractory chronic graft-versus-host disease: a multicenter real-world analysis - Joseph Pidala; Jongphil Kim; Denise Kalos; Corey Cutler; Zachariah DeFilipp; Mary E. D. Flowers; Betty K. Hamilton; Kuo-Kai Chin; Marcello Rotta; Najla El Jurdi; Mehdi Hamadani; Gulrayz Ahmed; et al. (Blood Advances)
Abstract: To examine the activity of ibrutinib in steroid-refractory chronic graft-versus-host disease (SR-cGVHD) after the US Food and Drug Administration approval, we conducted a multicenter retrospective study. Data were standardly collected (N = 270 from 19 centers). Involved organs included skin (75%), eye (61%), mouth (54%), joint/fascia (47%), gastrointestinal (GI) (26%), lung (27%), liver (19%), genital (7%), and others (4.4%). The National Institutes of Health (NIH) severity was mild in 5.7%, moderate 42%, and severe 53%. Thirty-nine percent had overlap subtype. Karnofsky performance status (KPS) was ≥80% in 72%. The median prednisone was 0.21 mg/kg (0-2.27). Ibrutinib was started at a median of 18.2 months after cGVHD onset and in earlier lines of therapy (second line, 26%; third, 30%; fourth, 21%; fifth, 9.6%; sixth, 10%; seventh or higher, 1.2%). Among evaluable patients, the 6-month NIH overall response rate (ORR; complete response [CR]/partial response [PR]) was 45% (PR 42%; CR 3%). The median duration of response was 15 months (range, 1-46). Liver involvement had association with 6-month ORR (multivariate [MVA] odds ratio, 5.49; 95% confidence interval [CI], 2.3-14.2; P < .001). The best overall response was 56%, with most (86%) achieving by 1 to 3 months. With a median follow-up for survivors of 30.5 months, failure-free survival (FFS) was 59% (53%-65%) at 6 months and 41% (36%-48%) at 12 months. On MVA, increased age (hazard ratio [HR], 1.01; 95% CI, 1.0-1.02; P = .033), higher baseline prednisone (HR, 1.92; 95% CI, 1.09-3.38; P = .032), and lung involvement (HR, 1.58; 95% CI, 1.1-2.28; P = .016) had worse FFS. Ibrutinib discontinuation was most commonly due to progressive cGVHD (44%) or toxicity (42%). These data support that ibrutinib has activity in SR-cGVHD, provide new insight into factors associated with response and FFS, and demonstrate the toxicity profile associated with discontinuation.